ANALISIS SISTEM AKUNTANSI PENGGAJIAN DAN PENGUPAHAN KARYAWAN DALAM MENINGKATKAN EFEKTIVITAS PENGENDALIAN INTERNAL PERUSAHAAN PADA PT. TRI MARBAKO - Citra Indah Merina; Mentari Bunga Herfazalesa (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study aims to determine the payroll and wage accounting system that is applied to increase the effectiveness of internal control at PT. Tri Marbako. The research method used is qualitative descriptive method. The data of this research are primary data and secondary data. Data collection techniques used are interviews, documentation and observation. The data analysis technique used is by comparing the payroll and wage accounting systems at PT. Tri Marbako with Mulyadi's theory of payroll and wage accounting systems and conducted a comparative analysis of payroll and wage accounting systems at PT. Tri Marbako. The results showed that the application of the payroll and wage accounting system at PT. Tri Marbako in improving the effectiveness of internal control is not appropriate. This is indicated by the disclosure of duties in the timekeeping function as well as making a list of salaries and wages, as well as incomplete accounting records used